TLC Monitoring on The Auto Reduction-Oxidation Reaction of Benzaldehyde Derivatives in Alcohol-Water as Solvent System - Rohmawati, Dini; Handayani, Sri; Budimarwanti, Cornelia; Handayani, Dina Wahyu; Puspitasari, Febrian Ayu; Puspitasari, Kirei Irawanti Muthmainnah (Indonesian Journal of Chemistry and Environment, 2025)
Autoreduction-oxidation reactions of benzaldehyde derivatives could be done without solvent, solventless, and with solvent conditions. Green solvents are one method to reduce the use of nonenvironmentally friendly solvents by considering their effectiveness in yielding. Benzaldehyde derivatives and NaOH were reacted in comparison of 1 : 1 with various alcohol-aquadest (0%, 20%, 50%, 80%, and 100%) as solvent system. The procedure for this disproportionation reaction is focused on grinding and ultrasonic-assisted methods. Both procedures could be applied under all solvent conditions along with the effective and efficient processes hence it corresponds to the green chemistry principles and sustainable development goals (SDGs). This article discussed the monitoring of product reaction using thin layer chromatography (TLC) techniques to evaluate the procedures of grinding and ultrasonic-assisted on the disproportionation reactions, which later could be used as standard procedures according to green chemistry and sustainable development goals (SDGs).